Inside Cover: Insights into the Crystallisation Process from Anhydrous, Hydrated and Solvated Crystal Forms of Diatrizoic Acid (Chem. Eur. J. 3/2015). Issue 3 (12th January 2015) - Fucke, Katharina; McIntyre, Garry J.; Lemée‐Cailleau, Marie‐Hélène; Wilkinson, Clive; Edwards, Alison J.; Howard, Judith A. K.; Steed, Jonathan W.
<x xml:space="preserve">Abstract</x> The clinically used X‐ray contrast agent diatrizoic acid exhibits 14 crystal forms including hydrates and solvates. Structural investigations using neutron and X‐radiation in connection with crystal lattice energy calculations give insight into the strength and interplay of hydrogen and halogen bonding for stabilisation of the lattice. The conformation of the molecule and the crystal packing is directly influenced by the solvation of the crystal form. For more details, see the Full Paper by K. Fucke et al. on page 1036 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>